2006
DOI: 10.1523/jneurosci.2741-06.2006
|View full text |Cite
|
Sign up to set email alerts
|

Cue-Invariant Networks for Figure and Background Processing in Human Visual Cortex

Abstract: Lateral occipital cortical areas are involved in the perception of objects, but it is not clear how these areas interact with first tier visual areas. Using synthetic images portraying a simple texture-defined figure and an electrophysiological paradigm that allows us to monitor cortical responses to figure and background regions separately, we found distinct neuronal networks responsible for the processing of each region. The figure region of our displays was tagged with one temporal frequency (3.0 Hz) and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
143
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(157 citation statements)
references
References 62 publications
14
143
0
Order By: Relevance
“…The shape representation in the LOC is also tuned for small shape changes in the outline of objects (Gillebert et al, 2009;Panis et al, 2008). Our previous source-imaging studies using frequency tagging have suggested that the LOC is tuned for the configuration of a small figure on a larger background (Appelbaum et al, 2010) and that LOC responses to figures are largely cue-invariant (Appelbaum et al, 2006(Appelbaum et al, , 2012. Cue-invariance in LOC has also been found with fMRI (Grill-Spector et al, 1998).…”
Section: Tuning For Shapementioning
confidence: 70%
See 2 more Smart Citations
“…The shape representation in the LOC is also tuned for small shape changes in the outline of objects (Gillebert et al, 2009;Panis et al, 2008). Our previous source-imaging studies using frequency tagging have suggested that the LOC is tuned for the configuration of a small figure on a larger background (Appelbaum et al, 2010) and that LOC responses to figures are largely cue-invariant (Appelbaum et al, 2006(Appelbaum et al, , 2012. Cue-invariance in LOC has also been found with fMRI (Grill-Spector et al, 1998).…”
Section: Tuning For Shapementioning
confidence: 70%
“…In the interest of brevity, we provide an overview of these methods, and reference the reader to our previous work (Ales and Norcia, 2009;Appelbaum and Norcia, 2009;Appelbaum et al, 2006Appelbaum et al, , 2008 for a more a more detailed description.…”
Section: Eeg Recordingmentioning
confidence: 99%
See 1 more Smart Citation
“…To test our hypothesis, we combined high-density electroencephalography (EEG) with anatomical and functional magnetic resonance imaging (fMRI) to characterize the population responses to these configurations in different regions of interest (ROIs; Appelbaum et al, 2006;Cottereau et al, 2011a,b). Observers were cued to attend to one of two target-surround stimuli that were presented to the left and right of fixation (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The SSVEP, the oscillatory response of the cortex to a flickering stimulus with the same temporal frequency as the initiating stimulus, provides a continuous measure of cortical activation patterns related to the processing of a frequency-tagged stimulus (Mü ller and Hillyard, 2000). Importantly, stimuli presented at different driving frequencies (in our case, background and object) evoke unique and separable brain responses (Appelbaum et al, 2006). SSVEPs have been used to investigate fundamental visual processes (Nakayama and Mackeben, 1982), visual attention , and object recognition (Kaspar et al, 2010).…”
Section: Introductionmentioning
confidence: 99%